USING THE ZOPA MODEL TO SYNERGIZE THE DIFFERENT INTERESTS OF LOCAL AND CENTRAL AUTHORITIES IN AN ADAPTIVE CITY PLAN TOWARDS FLOOD RESILIENCE IN SURAKARTA CITY, INDONESIA - Miladan, Nur; Permana, Ariva Sugandi (My University, 2020)
Surakarta City, a secondary city in Indonesia, has been threatened by floods for many decades due to the overflow of rivers and an inadequate urban drainage system. On top of that, inelastic time-bound city planning has made the city susceptible to ever-increasing flood threats. The local authority has attempted to minimize flood risk through particular structural mitigations of the urban drainage system, which it has authority to do, while the overall responsibility for flood control and river management is under central authority. The different responsibilities of these two different levels of authority have led to gaps and overlaps in relation to the same objects of interest. On one hand, the city authority is concerned with city planning, and on the other hand, the flood control and river management authority is responsible for combatting flooding problems and river management within the watershed. This issue is an interesting point to investigate. In order for Surakarta to become a resilient city, it is imperative to synergize the efforts of these two different levels of authorities. This study aims to find the synergistic and optimal solutions by means of a negotiated planning and management system that involves both authorities. Critical evaluation and assessment of relevant documents, field observations, and measurements, as well as acquiring expert opinions were the main methods used in this study. We propose a ZOPA (Zone of Possible Agreement) model to optimize agreement among the stakeholders. The model essentially highlights the common interests and sets aside the conflicting points among stakeholders. The study found that there are potential points to negotiate with regard to the division of responsibilities through a shared vision of the coordinated institutions and shared planning and management in the direction of synergistic determination.
Keywords: adaptive urban planning; flood risks; flood-resilient city; Indonesia; Surakarta; synergistic determination